Women of Medieval Russia: Possibilities and limits of Russian gender history - Komendová, Jitka (Dějiny – teorie – kritika, 2006)
The article deals with one of the trends in contemporary Russian historiography - gender history, specifically gender history of medieval Russia. The source base for research into the gender aspects of Russian society up to the 15th century is of a specific nature and is far less extensive and diverse than the materials coming from the Catholic part of Europe, which means that many of the problems that arouse the interest of historiography in the West are intractable in Russia. Although there is an intense debate on gender history among Russian academics, as among their Western colleagues, the research itself tends to be narrowed to women's history (istorichesaya feminologiya). The excessive focus of research on women's topics is manifested not only in relation to their male counterparts, but also in a certain isolation from other research on the history of medieval Russia. Russian gender history is now heavily oriented towards diachronic aspects and the study of individual isolated topics over very long periods of time, sometimes even millennia. One of the main tasks of contemporary gender-oriented medieval studies is therefore to pay more attention to synchronic aspects, i.e. to integrate gender themes into the picture of a particular epoch with all its specific cultural and social features and climate of thought.